(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Stem cell therapy has grown in popularity and complexity in recent years. Therapy has provided hope. This paper discusses stem cell discovery and treatment. Stem cells may be generated and altered in a lab. Teratoma formation and quality control assays help characterize stem cells. Use extraction and culture medium to optimize controlled differentiation. Graphene scaffolds and extracellular vesicle-based treatments may be applied in numerous stem tissue applications, therefore they need attention. The review summarizes stem cell treatment’s challenges before global usage. This breakthrough therapy brings hope to the ailing.